Solidarity or Sovereignty? EU Cooperation in Civil Protection - Ekengren, Magnus; Matzén, Nina; Rhinard, Mark; Svantesson, Monica (Journal of European Integration, 2006)
Civil protection is one of the more established European competences within the emerging protection policy space. It is also emblematic of an enduring tension within European politics. European Union states acknowledge the need to work closely to address pressing common issues. Yet those same states retain a tight grip on EU policy activities so as to protect their national sovereignty. That tension is apparent in the adopted 'solidarity declaration' from 2004, in which member states vow to assist one another in a disaster, and in the development of the EU's civil protection competences, where member states have carefully controlled their delegation of powers. This article explores how this tension manifests itself 'on the ground', in the actual operation of civil protection missions. Two cases are analysed - the 2002 floods in Central Europe and the 2004 Asian tsunami - in order to understand how member states acted collectively through EU structures and with what effect on the EU's disaster response effectiveness. By exploring member states' contributions to joint efforts, how those efforts were organized and what lessons were learned for future development, light is shed on how sovereignty concerns may prove to be an obstacle to solidarity.